Assessment of potential drug-drug interactions in hospitalized patients with infectious diseases: an experience from a secondary care hospital [version 4; peer review: 2 approved, 2 not approved] - Padma G.M. Rao; Rashid Ain Ur; Sathvik Belagodu Sridhar; Abu Nawa Ahmad Ismail; Javedh Shareef (F1000Research)
Background Polypharmacy is common among hospitalized patients with infectious infections owing to comorbidities or concurrent illnesses. This raises the likelihood of drug-drug interactions and creates uncertainty for healthcare providers. This study aimed to assess the potential drug-drug interactions (pDDIs) among hospitalized patients with infectious diseases in a secondary care hospital. Methods A prospective observational study was conducted in the internal medicine ward for six months. Data were collected from patient case records, and prescriptions were screened for pDDIs and classified based on the severity from a portable electronic physician information database (PEPID) resource analyzed using SPSS, version 27.0. Results In total, 148 patient case records were analyzed, and 549 pDDIs were identified, with 66.8% having at least one or more DDIs. The mean number of drug interactions was 3.70 ± 4.58 per prescription. The most frequently encountered drug interactions were drug combinations such as bisoprolol with atorvastatin and aspirin with tazobactam/piperacillin. Based on the severity, most pDDIs belong to the ‘moderate’ category (40.07%). Bivariate analysis showed that age, comorbidities, length of hospital stay, and the number of drugs prescribed were risk factors associated with DDIs (p<0.05). In the multiple binary logistic regression analysis, DDIs were significantly associated with comorbidities and the number of prescribed medications (p<0.0001). Conclusions This study observed the prevalence of DDIs in hospitalized patients with infectious diseases of ‘moderate’ severity. Prescription screening using a drug information database assists in identifying and preventing DDIs early, enhancing drug safety and quality of patient-centered care.